Detection of transovarial dengue viruses in Aedes albopictus from selected localities in Kuching and Samarahan divisions, Sarawak, Malaysia by reverse transcription polymerase chain reaction (RT-PCR) - Nor Aliza Abdul Rahim,; Harvie Shukri,; Nur Ain Mardiah Rizuan,; Lela Suut,; Siti Fairouz Ibrahim,; Razitasham Safii,; Marlini Othman, (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2019)
The current study reports the first detection of transovarial dengue virus in the adult of Aedes albopictus raised from immatures including eggs and larvae, collected from December 2014 to February 2016 by using black ovitrap from selected localities in Kuching and Samarahan Divisions, Sarawak. The mosquitoes were screened in the laboratory by using a conventional method of reverse transcription polymerase chain reaction (RT-PCR). Dengue virus serotype 1 (DENV-1) and 2 (DENV-2) were detected in two of the mosquito pools comprising of adult females Ae. albopictus which emerged from the immatures. None of the Ae. albopictus male mosquitoes were detected with dengue virus. Our findings revealed the first natural evidence of the transovarial transmission in the natural population of Ae. albopictus at the selected localities. This discovery may aid in establishing more strategic and effective control of Aedes mosquitoes and may also open more discussion and research on the persistency of dengue viruses in the environment via the vertical or transovarial transmission mainly in Sarawak.